The VIATICUM (Investigasi Historis-Yuridis) - Marrus, David Morrison; Piter, Romanus (STP St. Bonaventura Medan, 2024)
The aim of this research is to provide a comprehensive explanation of Viaticum in the Catholic Church. The explanation of Viaticum given is mainly in historical and juridical aspects. Viaticum is the Holy Eucharist received by people who will leave this mortal world and prepare themselves for the journey to eternal life in heaven. In simple terms, Viaticum is understood as sacred provisions for going to heaven. Here the author uses qualitative research methods with literature and argumentative review techniques to investigate historical and juridical aspects regarding Viaticum. Historical-juridical investigation itself is an approach or method that can be used to conduct scientific studies regarding canon law. The findings in this research are (1) Viaticum has a long and complex history and in that history there were debates and disagreements from the Church Fathers to formulate the correct rules regarding how sacred provisions were given to people who were sick and facing death; (2) canon law establishes clear and strict rules for people who receive and receive viticum, however there are concessions and dispensations in case of urgent and emergency situations; (3) Viaticum inherits the tradition of people's piety which is visible in the custom of visitation, exposition and procession of the Sacrament which is called